Degradation of river ecological quality in Tibet plateau with overgrazing: A quantitative assessment using biotic integrity index improved by random forest - Lihua Niu (Elsevier, 2021)
The river ecosystem in fragile regions is especially vulnerable to environmental or anthropogenic stressors. The ecological quality and stability of rivers in fragile regions urgently need to be evaluated before the reasonable protection and restoration. In this study, a random-forest-modified bacterial index of biological integrity (RF-BaIBI) was developed for ecological assessment of fragile rivers in the sources of Yangtze River and Yellow River (abbreviated as SYY) in Tibet Plateau, China. Three key bacterial metrics including Enterobacteriale, Fluviicola, and Oxalobacteraceae, were selected for the development of RF-BaIBI using range, responsiveness, redundancy tests, as well as random forest. The weight coefficients of metrics were calculated based on their relative importance to RF-BaIBI: Enterobacteriale (0.41), Fluviicola (0.34) and Oxalobacteraceae (0.25). The feasibility of RF-BaIBI was confirmed by its significant correlation with comprehensive environmental index (R2 = 0.71). Among 45 river sections, those with high or good status accounted for 26%, with moderate 51% and poor 13%. Redundancy and path analysis revealed that livestock grazing density was the most dominant factor influencing ecological conditions of the SYY. Under the pressure of grazing, rivers in the source of Yangtze River displayed higher stability than that of Yellow River via the resistance and co-occurrence network analyses. Compared to that of Yellow River, bacterial communities from the source of Yangtze River exhibited stronger competitive interaction which is very beneficial to the stability of the ecosystem. This study highlighted the great effect of overgrazing on the degradation of river ecological health status in Tibet Plateau based on the quantitative assessment of biotic integrity index, which provides a theoretical basis for the management of grazing in fragile plateau regions.